Is There a Relationship Between Maxillary Sinus Findings and Skeletal Malocclusion? - Sertac Aksakalli; Berza Sen Yilmaz; Muhammet Birlik; Ferit Dadasli; Esra Bolukbasi (Galenos Yayinevi, 2015)
Objective:No study has investigated the relationship between maxillary sinus findings and skeletal malocclusion based on conebeam computed tomography (CBCT). The objectives of this study were to determine the relationship between the frequency of sinus findings and patients' skeletal malocclusion classification.Materials and Method:A total of 105 CBCTscans were examined and divided into 3 groups according to skeletal classification. Two experienced observers reviewed the CBCT images and recorded all maxillary sinus findings. The patients' skeletal malocclusion, the thickness of the Schneiderian membrane, and the pathologic sinus findings were evaluated.Results:The sinus findings were classified into 4 groups: 0 = no finding, 1 = mucosal thickening, 2 = partial opacification with liquid accumulation, and 3 = total opacification. The statistical analysis showed that there was no correlation between the skeletal malocclusion and pathological sinus findings. However, there were significant differences in the Schneiderian membrane thicknesses between the groups.Conclusion:The Schneiderian membrane thickness was significantly different for Class II and Class III patients. There was no relationship between pathological sinus findings and skeletal malocclusions.